The GPCR properties of polycystin-1- A new paradigm - Maser, Robin L.; Calvet, James P.; Parnell, Stephen C. (Frontiers in Molecular Biosciences, 2022)
Polycystin-1 (PC1) is an 11-transmembrane (TM) domain-containing protein encoded by the PKD1 gene, the most frequently mutated gene leading to autosomal dominant polycystic kidney disease (ADPKD). This large (>462 kDal) protein has a complex posttranslational maturation process, with over five proteolytic cleavages having been described, and is found at multiple cellular locations. The initial description of the binding and activation of heterotrimeric Gαi/o by the juxtamembrane region of the PC1 cytosolic C-terminal tail (C-tail) more than 20 years ago opened the door to investigations, and controversies, into PC1’s potential function as a novel G protein-coupled receptor (GPCR). Subsequent biochemical and cellular-based assays supported an ability of the PC1 C-tail to bind numerous members of the Gα protein family and to either inhibit or activate G protein-dependent pathways involved in the regulation of ion channel activity, transcription factor activation, and apoptosis. More recent work has demonstrated an essential role for PC1-mediated G protein regulation in preventing kidney cyst development; however, the mechanisms by which PC1 regulates G protein activity continue to be discovered. Similarities between PC1 and the adhesion class of 7-TM GPCRs, most notably a conserved GPCR proteolysis site (GPS) before the first TM domain, which undergoes autocatalyzed proteolytic cleavage, suggest potential mechanisms for PC1-mediated regulation of G protein signaling. This article reviews the evidence supporting GPCR-like functions of PC1 and their relevance to cystic disease, discusses the involvement of GPS cleavage and potential ligands in regulating PC1 GPCR function, and explores potential connections between PC1 GPCR-like activity and regulation of the channel properties of the polycystin receptor-channel complex.